Experimental and theoretical studies of sea ice effects on internal solitary waves - Tan, Jin (Frontiers in Marine Science, 2024)
Internal solitary waves in polar regions attract much interest recently. It is important to understand how sea ice affects them, as that may have a profound influence on human activities and environment. In this study, experiments on internal solitary waves and two types of sea ice (ice sheet and ice keel) are presented. After showing that the Korteweg-de Vries (KdV) equation is more suitable than the Benjamin-Ono (BO) equation for simulating the waves studied, this paper presents corresponding simulations using the variable-coefficient Korteweg-de Vries (vKdV) equation, a derivation of the KdV equation. The sharp vertices of the ice result in occasional inconsistency with the vKdV predictions. Nonetheless, the vKdV equation is still suitable for modelling such waves under sea ice, giving generally accurate results that are adequate to assist further studies. Both experiments and simulations provide evidence for wave deformation, oscillation occurring in the rear of the wave, and decrease in amplitude. The latter suggests possibilities of energy dissipation or emission of small amplitude linear waves. This is for the first time that the vKdV equation is applied to investigate the impacts of sea ice on internal solitary waves.